Death Penalty For Drug Traffickers: A Legal and Human Rights Perspective - Supono, Supono; Kristiawanto, Kristiawanto; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2024)
The increase in drug abuse cases in Indonesia has placed the death penalty for dealers as one of the instruments of criminal law policy. Although the death penalty aims to provide a deterrent effect and justice, this policy has drawn criticism because it is considered contrary to the principles of human rights (HAM) and has the potential to create disparities in its application. This research analyses the application of the death penalty from the perspective of absolute, relative, and combined punishment theories, as well as evaluating its effectiveness in handling narcotics cases. The results show that the application of the death penalty needs to be reconsidered, especially for non-violent offenders, by prioritising rehabilitation and prevention approaches. A combination of legal and rehabilitation strategies is needed to minimise the use of the death penalty, accompanied by continuous monitoring and evaluation to ensure transparency and accountability in law enforcement. This research recommends more sustainable policy alternatives, in line with human rights values and social justice.